2019
DOI: 10.3389/fpsyg.2019.01953
|View full text |Cite
|
Sign up to set email alerts
|

Generational Diversity in the Workplace: Psychological Empowerment and Flexibility in Spanish Companies

Abstract: Intergenerational diversity is a universal fact in sustainability and today’s work environment. Current studies seek to find differences that exist between these generational groups that coexist, cooperate, and sometimes compete in business organizations. Sixteen focus groups have taken place, four for each generation to find the differences that may exist depending on that group membership. Specifically, the psychological empowerment and psychological flexibility variables have been analyzed, which have alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Similar results were suggested by [ 64 ], who indicated that increased frequency of violence implies a greater acceptance of abuse, all of which is reinforced by the presence of sexist attitudes in the victims who hide the situation of abuse they are living with because they consider such abuse to be normal behaviour. The link between sexism and romantic love highlighted by such authors as [ 72 , 73 ] could be the key to understanding this phenomenon, even more so considering that it is the girls who show greater idealization of love, while boys tend to adopt a paternalistic vision of care and dependence with respect to their partner [ 74 ]. With this, sexist attitudes could activate certain mechanisms in a victim that stop them from labeling themself as abused.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were suggested by [ 64 ], who indicated that increased frequency of violence implies a greater acceptance of abuse, all of which is reinforced by the presence of sexist attitudes in the victims who hide the situation of abuse they are living with because they consider such abuse to be normal behaviour. The link between sexism and romantic love highlighted by such authors as [ 72 , 73 ] could be the key to understanding this phenomenon, even more so considering that it is the girls who show greater idealization of love, while boys tend to adopt a paternalistic vision of care and dependence with respect to their partner [ 74 ]. With this, sexist attitudes could activate certain mechanisms in a victim that stop them from labeling themself as abused.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, association with other agents has turned to innovation (Sobrino et al, 2019), challenging traditional concepts by encouraging firms to break with conventions and existing thought patterns through open innovation in which companies integrate both internal and external knowledge flow. This motivates internal innovation as well as enabling firms to seek out external channels in order to commercialize outcomes with the core idea of integrating knowledge, skills, and ideas from the public (Chesbrough, 2003a,b).…”
Section: Cooperation With Universities and Performancementioning
confidence: 99%
“…During the last few decades, the development of the internet and data analysis (Geczy et al, 2014), the abundance of available information (Southwell, 2005), globalization (Mark, 1996), and increased consumer power (Kucuk, 2008), or what is known as the sharing economy (Belk, 2018), have brought about dramatic changes that affect people and organizations (Sobrino et al, 2019), as well as have negative environmental impacts. In response, environmental issues have become a top priority for governments, which, through regulations and fiscal incentives, among others, have been promoting "eco-innovations" (OECD, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Westerman and Yamamura (2007) found a lower level of job satisfaction among baby boomers than generation X and Y. Other researchers also reported significant intergenerational variation across a variety of work behaviors like work values (Bennett et al, 2012;Smola and Sutton, 2002;Yogamalar and Samuel, 2016), work ethics and motivation (Soto and Lugo, 2013;Zemke et al, 2000;Olson and Brescher, 2011), learning orientation (D'Amato and Herzfeldt, 2008), psychological empowerment and flexibility (Toro et al, 2019), use of influence tactics (Landry, 2009) intention to leave the job (Benson and Brown, 2011) and narcissism (Trzesniewski and Donnellan, 2010). These differences have a significant effect on the successful implementation of HR policies and practices of an organization.…”
Section: Introductionmentioning
confidence: 97%
“…, 2012; Smola and Sutton, 2002; Yogamalar and Samuel, 2016), work ethics and motivation (Soto and Lugo, 2013; Zemke et al. , 2000; Olson and Brescher, 2011), learning orientation (D'Amato and Herzfeldt, 2008), psychological empowerment and flexibility (Toro et al. , 2019), use of influence tactics (Landry, 2009) intention to leave the job (Benson and Brown, 2011) and narcissism (Trzesniewski and Donnellan, 2010).…”
Section: Introductionmentioning
confidence: 99%